2016
DOI: 10.1038/eye.2015.266
|View full text |Cite
|
Sign up to set email alerts
|

Does infrared or ultraviolet light damage the lens?

Abstract: In daylight, the human eye is exposed to long wavelength ultraviolet radiation (UVR), visible radiation and short wavelength infrared radiation (IRR). Almost all the UVR and a fraction of the IRR waveband, respectively, left over after attenuation in the cornea, is absorbed in the lens. The time delay between exposure and onset of biological response in the lens varies from immediate-to-short-to-late. After exposure to sunlight or artificial sources, generating irradiances of the same order of magnitude or sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…Different risk factors are known for this disease, for example diabetes (Xu et al 2016), but one of the main and most diffused risk factor is long-term ultraviolet (UV) radiation exposure. Both UV-A and UV-B are absorbed by the lens and act with different mechanisms in inducing cataractogenesis, with a progressive chronic photochemical damage (West 1999;L€ ofgren 2016;S€ oderberg et al 2016). The lens nucleus is particularly susceptible to UV-A-induced stress, able to determine changes in the lens fluorescence, increased yellowing and loss of pyridine nucleotides (Linetsky et al 2014), by modulating gene expression and apoptotic stimuli in the lens epithelial cells (Andley et al 2000(Andley et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Different risk factors are known for this disease, for example diabetes (Xu et al 2016), but one of the main and most diffused risk factor is long-term ultraviolet (UV) radiation exposure. Both UV-A and UV-B are absorbed by the lens and act with different mechanisms in inducing cataractogenesis, with a progressive chronic photochemical damage (West 1999;L€ ofgren 2016;S€ oderberg et al 2016). The lens nucleus is particularly susceptible to UV-A-induced stress, able to determine changes in the lens fluorescence, increased yellowing and loss of pyridine nucleotides (Linetsky et al 2014), by modulating gene expression and apoptotic stimuli in the lens epithelial cells (Andley et al 2000(Andley et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Exposure to UVR from sunlight has been mainly associated with the risk of age-related cortical cataract. 13 16 Climatic UVR has been positively correlated with cataract prevalence in the Indigenous Australian population. 6 …”
mentioning
confidence: 99%
“… 18 Although the procedure involved long-term (30 minutes of) exposure to UVA light, this study showed that the changes observed using SD-OCT and mfERG are not similar in nature or magnitude to other phototoxicity conditions described previously. This difference could be explained by the protective features of the anterior segment 25 , 26 and the low UVA light intensity of the procedure relative to the intensity associated with typical phototoxicity conditions. The SD-OCT findings also reflected an increase in central macular thickness, which is the opposite of the typical thinning seen in outer retinal abnormalities.…”
Section: Discussionmentioning
confidence: 99%